Costs and Clinical Quality Among Medicare Beneficiaries: Associations with Health Center Penetration of Low-Income Residents - Sharma, Ravi (Centers for Medicare & Medicaid Services, 2014)
OBJECTIVE: Determine the association between access to primary care by the underserved and Medicare spending and clinical quality across hospital referral regions (HRRs). DATA SOURCES: Data on elderly fee-for-service beneficiaries across 306 HRRs came from CMS’ Geographic Variation in Medicare Spending and Utilization database (2010). We merged data on number of health center patients (HRSA’s Uniform Data System) and number of low-income residents (American Community Survey). STUDY DESIGN: We estimated access to primary care in each HRR by “health center penetration” (health center patients as a proportion of low-income residents). We calculated total Medicare spending (adjusted for population size, local input prices, and health risk). We assessed clinical quality by preventable hospital admissions, hospital readmissions, and emergency department visits. We sorted HRRs by health center penetration rate and compared spending and quality measures between the high- and low-penetration deciles. We also employed linear regressions to estimate spending and quality measures as a function of health center penetration. PRINCIPAL FINDINGS: The high-penetration decile had 9.7% lower Medicare spending ($926 per capita, p=0.01) than the low-penetration decile, and no different clinical quality outcomes. CONCLUSIONS: Compared with elderly fee-for-service beneficiaries residing in areas with low-penetration of health center patients among low-income residents, those residing in high-penetration areas may accrue Medicare cost savings. Limited evidence suggests that these savings do not compromise clinical quality.